Implications Of Filling The Position Of Attorney General By The President On The Independence Of The Prosecutor's Office In Carrying Out The Functions Of Judicial Power - Sukamto Satoto; Ardilafiza Ardilafiza; Riky Musriza (Ipso Jure, 2024)
This research aims to find out and understand the influence of the current mechanism for filling the position of Attorney General on the independence of the Prosecutor's Office in carrying out law enforcement functions. The research results show that The implementation of the mechanism for filling the position of Attorney General who is appointed and dismissed by the President has two consequences. Firstly, it opens up opportunities for intervention in the law enforcement function by the President, carried out with various motives and interests, thus affecting the independence of the law enforcement function of the Prosecutor's Office. The two positions of Attorney General were then held from non-Prosecutor professions and even held by political party cadres which influenced the impartiality and professionalism of the implementation of law enforcement functions by the Prosecutor's Office